Design and development of a high frequency Mosfet driver - Swart, Arthur James (My University, 2004)
A high-power Mosfet was incorporated as a switching device into the efficient Class E configuration, where the switching device switches current through itself either completely on or completely off at high frequencies. The first objective of this project was to demonstrate the effectiveness of a phase-lock loop circuit in generating stable high frequencies when connected in an indirect frequency synthesizer configuration. The indirect frequency synthesizer has established itself as a versatile frequency generator capable of generating high frequencies based on a lower stable reference frequency. The frequency generation stage incorporates a phaselock loop circuit, a frequency divider and a stable reference frequency section. The phase-lock loop section incorporates the TTL based 74HC 4046 that is based upon the common CMOS 4046 integrated circuit. The frequency divider section is built around the CMOS-based 4526 whilst the reference frequency section incorporates the CMOS-based 4060. The frequency synthesizer produced a range of frequencies from 50 kHz to 8 MHz in 50 kHz steps. The output voltage was constant at 5,5 V. The second objective was to show that the complementary emitter follower is indeed a worthy Mosfet gate drive circuit at high frequencies. The Mosfet driver stage produced a voltage signal of at least 11 V, being able to source and sink relatively high peaks of current, especially at high frequencies. Voltage amplification occurred through the use of multiple CMOS-based 40106 inverters. The complementary emitter follower, known for its low output impedance and its ability to source and sink large amounts of current, was an important component in the final Mosfet gate section.
Thesis (M. Tech. Engineering: Electrical--Vaal University of Technology
Keywords: Mosfet; Switching device; 621.38412; Metal oxide semiconductor field-effect transistors; Radio frequency